The Impact of Digital Payment Systems on Federal Inland Revenue Service Revenue Generation in Nigeria - Manir umar; Aurelia Widya Astuti (Cakrawala Repositori IMWI)
The objective of this study is to analyze the impact of digital payment systems on the revenue generation of the Federal Inland Revenue Service (FIRS) in Nigeria. This research employs a quarterly dataset covering the period from the first quarter of 2009 to the last quarter of 2024. Utilizing the Autoregressive Distributed Lag (ARDL) technique for data analysis, the findings indicate that Remita Transfer (RMTA) and National Electronic Funds Transfer (NEFT) did not significantly affect FIRS revenue during the analyzed period. This suggests that these platforms may not be used effectively for tax-related transactions or lack sufficient transaction volume to impact overall revenue. Conversely, the results show that Web Pay has a significant positive impact on revenue generation, indicating that transactions processed through this platform are likely linked to taxable activities, thereby enhancing revenue collection. The success of Web Pay can be attributed to its user-friendly interface and reliability, which encourage increased taxpayer engagement in digital transactions. However, the study also found that Mobile Pay has a significant negative impact on FIRS revenue generation, potentially due to its lower adoption rate for tax-related transactions or challenges in tracking and reporting. Based on these findings, it is recommended that FIRS prioritizes Web Pay, promotes its adoption through targeted campaigns, and investigates the limitations of Remita and National Electronic Funds Transfer. Furthermore, a comprehensive assessment of Mobile Pay is required to identify and address its barriers, aiming to transform it into a more effective revenue-generating tool for FIRS.